Cross-sectional association study of hedonic hunger, self-control, cognitive distortion, and well-being with adiposity measures among a sample of urban Malaysian adults - Yee-How Say; Mimi Shamirah Nordin; Alvin Lai Oon Ng (BMC Psychology, 2024)
Abstract Background We assessed the association of hedonic hunger, self-control (impulsivity and restraint), cognitive distortion (CD), and well-being with adiposity measures such as waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), body mass index (BMI), total body fat (TBF), subcutaneous fat (SF), visceral fat level (VFL), skeletal muscle percentage (SM), and resting metabolism (RM), among a sample of urban Malaysian adults at Sunway University and Sunway College, Selangor, Malaysia. Methods Among 186 participants (M/F = 51/135; aged 22.1 ± 5.0), psychometrics were assessed using Power of Food Scale (PFS), Brief Self-Control Scale, CD Questionnaire (CD-Quest), and WHO-5 Well-being Index. Blood pressures, anthropometrics and body compositions were also measured using standard methods and bioimpedance. Results Men had significantly higher well-being, but lower overall self-control, impulsivity and Food Available hedonic hunger. Those with moderate/severe CD had higher odds ratio (OR) of having high central adiposity, compared with those with absent/slight CD (OR: 2.52;95% CI: 1.14, 5.61; p = 0.023 for WC and OR: 2.50; 95% CI: 1.19, 5.23; p = 0.015 for WHR). Higher CD and PFS scores were strongly significantly correlated with higher systolic blood pressure (SBP), WC, WHR, WHtR, BMI, TBF, SF, VFL and RM. Lower self-control was weakly correlated with higher WC, while lower impulsivity and restraint were weakly correlated with higher VFL. Those who were overweight, obese, and in high TBF class had significantly higher PFS Aggregate Factor scores. Food Available and Food Present scores, but not Food Tasted, were also significantly higher among overweight participants. Conclusions Higher hedonic hunger and CD were associated with higher SBP and all adiposity measures. Overweight participants had higher hedonic hunger in the context of ready availability and physical presence of highly palatable foods. Lower self-control was weakly correlated with higher central adiposity; lower impulsivity and restraint were weakly correlated with higher visceral adiposity. These findings have provided some insights into the cognitive factors underlying adiposity.